Towards Thin Calcium Metal Anodes—An Essential Component for High-Energy-Density Calcium Batteries - Christoph Kiesl; Reinhard Böck; Holger Kaßner; Joachim Häcker; Marco Kögel; Timo Sörgel; Şeniz Sörgel (Nanomaterials)
Metal anodes, such as those based on Ca, Mg, Na and Li, are considered to be one of the keys to the further development of high-energy-density rechargeable batteries. The thickness of these metal anodes directly affects the energy density of the battery. However, the fabrication of thin anodes poses technical challenges which often result in using excessively thick metal anodes in batteries. Here we present, for the first time, a study on the development of a thin Ca battery anode fabricated by electrodeposition. The battery anode with a thickness of approximately 10 µm corresponds to a charge density of 4.0 mAh cm−2. This study systematically investigates the electrodeposition behavior of Ca using a 1.0 M Ca(BH4)2 in THF as the electrolyte. A systematic evaluation of electrodeposition parameters—including substrate pretreatment, current density, hydrodynamics and charge density by area—is conducted. Scanning electron microscopy (SEM) and complementary image analysis provide detailed insights into these parameters. Electrodeposition offers a promising route to achieve a defined battery cell balance with minimal excess of metal at the anode. This will improve overall battery performance and efficiency. The findings contribute to the advancement of fundamental aspects of rechargeable batteries, particularly Ca-based batteries.